Ancient Greek Influence and Imagism In H.D's Early Poems - Djuhertati Imam Muhni (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1998)
In 1912 in the Museum-Street-Tea Shop Ezra Pound edited H.D's poem